(3GdeZfis - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs; (3YeQ Hf GdMSjf Hf YHO Gddg GdNQbj, CHh GdbGSe,J (B334 (3g` s
(3ChdgG (B:s
(3cJGH GdhOjYI , hGdCUd gfG GdcJGH hGdSfI hGdELeGY CeG GdcJGH ajbhd Gddg JYGdi (B" (3Ef Gddg jCeQce Cf JDOhG GdCeGfGJ Edi CgdgG(B" s
(3BNQgG (B:s
(3TQWG ddWdGb (B" (3HOhf TQWg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B44 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1626s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg MfHdi (B17) s
Keywords: (3Gdabg GdMfHdjs